Can soil organic carbon sequestration and the carbon management index be improved by changing the film mulching methods in the semiarid region? - Jialin Yang; Liangqi Ren; Nanhai Zhang; Enke Liu; Shikun Sun; Xiaolong Ren; Zhikuan Jia; Ting Wei; Peng Zhang (Journal of Integrative Agriculture, 2024)
Plastic film mulching has been widely used to increase maize yield in the semiarid area of China. However, whether long-term plastic film mulching is conducive to agricultural sustainability in this region remains controversial. A field experiment was initiated in 2013 with five different film mulching methods: (i) control method, flat planting without mulching (CK), (ii) flat planting with half film mulching (P), (iii) film mulching on ridges and planting in narrow furrows (S), (iv) full film mulching on double ridges (D), and (v) film mulching on ridges and planting in wide furrows (R). The effects on soil organic carbon (SOC) content, storage, and fractions, and on the carbon management index (CMI) were evaluated after nine consecutive years of plastic film mulching. The results showed that long-term plastic film mulching generally maintained the initial SOC level. Compared with no mulching, plastic film mulching increased the average crop yield, biomass yield, and root biomass by 48.38, 35.06, and 37.32%, respectively, which led to the improvement of SOC sequestration. Specifically, plastic film mulching significantly improved CMI, and increased the SOC content by 13.59%, SOC storage by 7.47% and easily oxidizable organic carbon (EOC) by 13.78% on average, but it reduced the other labile fractions. SOC sequestration and CMI were improved by refining the plastic film mulching methods. The S treatment had the best effect among the four mulching methods, so it can be used as a reasonable film mulching method for sustainable agricultural development in the semiarid area.